ProTrack: An Interactive Multi‐Omics Data Browser for Proteogenomic Studies. Issue 21 (6th August 2020) - Calinawan, Anna Pamela; Song, Xiaoyu; Ji, Jiayi; Dhanasekaran, Saravana Mohan; Petralia, Francesca; Wang, Pei; Reva, Boris
Abstract: The Clinical Proteomic Tumor Analysis Consortium (CPTAC) initiative has generated extensive multi‐omics data resources of deep proteogenomic profiles for multiple cancer types. To enable the broader community of biological and medical researchers to intuitively query, explore, and download data and analysis results from various CPTAC projects, a prototype user‐friendly web application called "ProTrack" is built with the CPTAC clear cell renal cell carcinoma (ccRCC) data set (http://ccrcc.cptac-data-view.org ). Here the salient features of this application which provides a dynamic, comprehensive, and granular visualization of the rich proteogenomic data is described.